ANALISA USAHA TANI BAWANG DAUN (Allium fistulusom L) DI KELURAHAN BINUANG KECAMATAN BINUANG KABUPATEN TAPIN KALIMANTAN SELATAN - Susmawati Susmawati (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2017)
The study aims:1. To determine the cost of farming system onion 2. To determine income of farming system onions 3. To determine whether the farm is worth it or not. This result was conducted in the experimintal BBPP Binuang for 3 months from April until the month of June 2016. Analysis of data used in this study :1). Analysis BEP Volume Production 2.)Analysis BEP Production Price 3.)Analysis B/C ratio 4.) Analysis of ROI. Production volume analysis result show 146,7 kg, the analysis results BEP price production show Rp. 11.404,11;the analysis results B/C ratio 1,31 show that the farm should be develoved onion, whereas the analysis results show 31,53 % ROI. The results of analysis of total cost production Rp.81.503.030, while the results of the analysis of the total revenue Rp.107.201.850;the results of cost analysis show profit each harvest of Rp.25.698.000